2019
DOI: 10.3389/frobt.2019.00110
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Personalization of an In-Home Socially Assistive Robot for Children With Autism Spectrum Disorders

Abstract: Socially assistive robots (SAR) have shown great potential to augment the social and educational development of children with autism spectrum disorders (ASD). As SAR continues to substantiate itself as an effective enhancement to human intervention, researchers have sought to study its longitudinal impacts in real-world environments, including the home. Computational personalization stands out as a central computational challenge as it is necessary to enable SAR systems to adapt to each child's unique and chan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 110 publications
1
63
0
4
Order By: Relevance
“…In further studies, robots should be endowed with an extensive set of educational goals and sensory options so that the administration of the educational procedure can be personalized. A first step toward this goal was recently made by Clabaugh et al ( 2019 ) who developed a fully autonomous robot, SPRITE, able to personalize its instruction and feedback to each child's proficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In further studies, robots should be endowed with an extensive set of educational goals and sensory options so that the administration of the educational procedure can be personalized. A first step toward this goal was recently made by Clabaugh et al ( 2019 ) who developed a fully autonomous robot, SPRITE, able to personalize its instruction and feedback to each child's proficiency.…”
Section: Discussionmentioning
confidence: 99%
“…To date, nearly 30 robots were tested as remedial tools for ASD [e.g., : Labo-1 (Werry et al, 2001 ); Muu (Miyamoto et al, 2005 ), Robota (Billard et al, 2007 ), FACE (Pioggia et al, 2007 ), Keepon (Kozima et al, 2007 ), Aibo (Francois et al, 2009 ), IROMEC (Iacono et al, 2011 ), Charlie (Boccanfuso and O'Kane, 2011 ), NAO (Shamsuddin et al, 2012 ), Flobi (Damm et al, 2013 ); GIPY-1 (Giannopulu, 2013 ), Pleo (Kim et al, 2013 ), KASPAR (Wainer et al, 2014 ), Darwin-OP (Peng et al, 2014 ), Pabi (Dickstein-Fischer and Fischer, 2014 ), Zeno (Salvador et al, 2015 ), Jibo (Guizzo, 2015 ), Probo (Simut et al, 2016 ), Maria (Valadao et al, 2016 ), Sphero (Golestan et al, 2017 ), CARO (Yun et al, 2017 ), KiliRo (Bharatharaj et al, 2018 ), MINA (Ghorbandaei Pour et al, 2018 ), QTrobot (Costa et al, 2018 ), Milo (Chalmers, 2018 ), Leo (She et al, 2018 ), Daisy (Pliasa and Fachantidis, 2019 ), SAM (Lebersfeld et al, 2019 ), SPRITE (Clabaugh et al, 2019 ), Actroid-F (Yoshikawa et al, 2019 ) etc.].…”
Section: Introductionmentioning
confidence: 99%
“…In a third possible definition, AI also empowers a "science of the artificial" (Simon, 1969(Simon, /1996 where innovators can create new learning environment configurations in order to study what the future could bring. Some examples include the possibility of students learning collaboratively with an artificial agent that facilitates their social interactions, for example, preschool-age children learning science with a social robot who motivates them and supports their inquiries (Kim et al, 2018), or differently-abled learners getting personalized support from a near-peer socially assistive robot buddy (Clabaugh et al, 2019). AI can also be a toolkit for building innovative approaches to assess students' competencies (Paquette, et al, 2014;Mislevy, et al, 2020) and the results can be used to support further learning.…”
Section: Defining Artificial Intelligencementioning
confidence: 99%
“…The importance of personalization in HRI is widely reported and impacts cooperation [2], overall acceptability [3,4] and interaction and engagement [2,5]. Indeed, an early review by Fong [6] on characteristics of successful socially interactive robots suggested that emotions, dialogue, and personality are crucial to facilitating believable HRI.…”
Section: Introductionmentioning
confidence: 99%